2004
DOI: 10.1016/j.ejvs.2004.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Sites of Implantation for Central Venous Access Devices (Ports): A Study of the Experiences and Preferences of Patients

Abstract: Many patients complain of few problems with their CVADs, regardless of site, but half have some persistent discomfort. Cosmetic considerations frequently cause concern and patients should be given choice in the site of their CVADs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 5 publications
(5 reference statements)
0
22
0
Order By: Relevance
“…It provides freedom to choose activities and favors body image (5,13,14) . However, some studies also show limitations and opposite feelings concerning such considerations (4,15) . This contradiction has also been found in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It provides freedom to choose activities and favors body image (5,13,14) . However, some studies also show limitations and opposite feelings concerning such considerations (4,15) . This contradiction has also been found in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…They had their physical appearance modified because of either the visible healing or the prominent catheter reservoir, consequently visible when wearing certain clothes. In another study, also carried out with this clientele, 44% of the patients showed alteration in their body image (15) . These aspects are present in the findings of this study: 50% of the critical incidents in this category.…”
Section: Discussionmentioning
confidence: 99%
“…From the literature search, a total of 25 publications were selected as appropriate for review (Table 2.2), including Oakley, Wright and Ream (2000); ; Chernecky (2001(;Campbell et al, (2004); Goossens et al, (2005); Kreis et al, (2007); Molloy, Smith and Aitchison, (2008); Nagel (2008); Martins et al, (2008); Johansson et al, (2009); ; Møller and Adamsen (2010); Yamada et al, (2010); Goltz et al, (2013); Sharp et al, (2014); Alpenberg, Joelsson and Rosengren, (2015); ; ; Burbridge and Goyal, (2016); Song and Oh, (2016); Yagi et al, (2016); Parás-Bravo et al, (2018); Ryan et al, (2019); Park and Lee, (2020).…”
Section: Literature Review Findingsmentioning
confidence: 99%
“…The quality appraisal of the studies resulted in a rating of strong for four studies (Ryan et al, 2019;Kreis et al, 2007;Møller and Adamsen, 2010;Nagel et al, 2012). Moderate for twenty studies (Oakley, Wright and Ream, 2000;Chernecky, 2001;Campbell et al, 2004;Goossens et al, 2005;Martins et al, 2008;Molloy, Smith and Aitchison 2008;Johansson et al, 2009;Yamada et al, 2010;Goltz et al, 2013;Sharp et al, 2014;Alpenberg, Joelsson and Rosengren, 2015;Song and Oh, 2016;Edström, Lindqvist and Rosengren, 2016;Burbridge and Goyal, 2016;Minichsdorfer, et al, 2016;Yagi et al, 2016;Park and Lee, 2020). One study was rated as weak .…”
Section: Literature Review Findingsmentioning
confidence: 99%
See 1 more Smart Citation